Davidee Piungnituq (1929-1993) - Wenzel, George W. (ARCTIC, 1994)
. Piungnituq was the quintessential spirit of inummariit, recognized as a hunter and provider, leader of his extended family after the death of his father, deeply religious and, above all, a loving spouse and parent. Throughout his life he studied the animals and land that he and his family depended upon, always instructing his sons and daughters by example. Each day of hunting ended with all the members of the Aqviqtiuq community gathering in his qangmaq to share in the day's harvest. And each evening, youngsters listened as he recounted the day, discussing the characteristics of the sea ice or the behavior of a polar bear, each "lesson" delivered isumasayuq (with wisdom). . In the course of time, Piungnituq, not surprisingly, drew the attention of scientist, journalists and ordinary travellers. . His exceptional work in whale bone, depicting aspects of Inuit culture and oral tradition, led to his first and only voluntary visit to "the South" - an exhibition of his art in Montreal in the mid-1970s. .